2007
DOI: 10.1016/j.jhydrol.2007.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of surface flow hydrology and sediment retention upslope of a vetiver buffer strip

Abstract: Vegetated buffer strips are widely used to reduce fluxes of eroding soil and associated chemicals, from hillslopes into waterways. Sediment retention by buffers is time-dependent, with its effectiveness changing with the deposition process. Our research focuses on settling of sediment upslope of stiff grass buffers at three slopes, under subcritical flow conditions. A new model is developed which couples the hydraulics, sediment deposition and subsequent adjustment to topography in order to predict water and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 24 publications
4
66
1
Order By: Relevance
“…Under the experimental conditions, fl ow retardation took place at a certain distance ahead of each grass strips, especially on the gentle slope, and most sediment deposited in the backwater region. Hussein et al(2007aHussein et al( , 2007b also reported that backwater region increased overall STE, and more than 90% of infl ow sediment was deposited upslope of a vetiver grass strip at 1~5% slopes and subcritical fl ow rates ≤0·001 m 3 m…”
Section: Resultsmentioning
confidence: 97%
“…Under the experimental conditions, fl ow retardation took place at a certain distance ahead of each grass strips, especially on the gentle slope, and most sediment deposited in the backwater region. Hussein et al(2007aHussein et al( , 2007b also reported that backwater region increased overall STE, and more than 90% of infl ow sediment was deposited upslope of a vetiver grass strip at 1~5% slopes and subcritical fl ow rates ≤0·001 m 3 m…”
Section: Resultsmentioning
confidence: 97%
“…Grasslands are also used to control the erosion of highly erodible lands [43,44]. Grasses are used in crop rotations and in strip cropping systems to slow surface water flow [45], to increase infiltration [46,47], and to reduce sediment running off tilled fields [48]. Despite this, it seems that the lands of study area were more suitable for agriculture than for grassland.…”
Section: Discussionmentioning
confidence: 99%
“…The length and depth of backwater for the same flow rate and vegetation type and density changes substantially with slope. Therefore, it is almost impossible to have sediment trapping upstream of the grass buffer strips in slopes more than 12% (Ghadiri et al, 2001;Hussein et al, 2007b).…”
Section: Area Of Depositionmentioning
confidence: 99%
“…A few physically-based models have been developed to predict the efficiency of vegetated buffer strips in sediment removal (Deletic, 2001b;Hussein et al, 2007b;Munoz-Carpena et al, 1999;Newham et al, 2005). Some currently available models are not completely process-based and their sediment transport and deposition sub-models are not very well validated (Munoz-Carpena et al, 1999;Newham et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation